Moduli Spaces of Metrics with Lower or Pinched Curvature Bounds and Their Compactifications (Journal of Mathematical Study, 2025)
We present a metric approach to the study of moduli spaces of metrics withcertain curvature bounds and suitable other geometric constraints, and their compactifications. This is accompanied by a deeper discussion of related results, questions andproblems in the realm of positive and positively pinched sectional as well as Ricci curvature. Regarding the latter two topics, we place special emphasis on correspondingworks and contributions of Rong X and his collaborators.